PERAN TEMAN SEBAYA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SMP SWASTA AL HIDAYAH - Eka Putri Nauliana; Evan Raja Natanael Siregar; Lovian Malona Manullang; Ida Mona Sidabutar; Tessalonik H A Hasugian (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the role of peers in improving students’ learning motivation at SMP Swasta Al Hidayah. This research used a descriptive qualitative approach, with data collected through interviews involving 15 students, consisting of 4 male students and 11 female students. The findings show that peers are not always the main factor that encourages students’ learning motivation. Most students stated that their willingness to study comes more from their own personal intention rather than direct encouragement or invitation from friends. However, peers still have a positive influence in certain situations, especially through examples of learning behavior. When one student starts doing assignments or paying attention to lessons, other students may feel encouraged to do the same. In addition, the role of peers becomes more visible during group work activities. Students cooperate, help each other, and explain learning materials to friends who do not yet understand the lesson, such as in English subjects. Students’ interest in certain subjects, such as Indonesian, Mathematics, English, and Arabic, also influences their enthusiasm for learning. Therefore, peers can be understood as learning supporters, although students’ main motivation is more strongly influenced by their own internal willingness.